2007
DOI: 10.1016/j.devcel.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Chk1 Is Required for Spindle Checkpoint Function

Abstract: The spindle checkpoint delays anaphase onset in cells with mitotic spindle defects. Here, we show that Chk1, a component of the DNA damage and replication checkpoints, protects vertebrate cells against spontaneous chromosome missegregation and is required to sustain anaphase delay when spindle function is disrupted by taxol, but not when microtubules are completely depolymerized by nocodazole. Spindle checkpoint failure in Chk1-deficient cells correlates with decreased Aurora-B kinase activity and impaired pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
227
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(249 citation statements)
references
References 37 publications
19
227
2
1
Order By: Relevance
“…Reduced Chk1 function in Pten-deficient cells leads to the accumulation of double-stranded DNA breaks and genetic instability, particularly at fragile sites (Puc and Parsons, 2005;Durkin et al, 2006). It was also shown that Chk1 has a regulatory role in the spindle checkpoint in chicken DT40 cells (Zachos et al, 2007) and in U2OS cells (Carrassa et al, 2009). Here, our data provide in vivo evidence that Chk1 is essential for the spindle checkpoint in mouse mammary epithelial cells and mammary cancer cells.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Reduced Chk1 function in Pten-deficient cells leads to the accumulation of double-stranded DNA breaks and genetic instability, particularly at fragile sites (Puc and Parsons, 2005;Durkin et al, 2006). It was also shown that Chk1 has a regulatory role in the spindle checkpoint in chicken DT40 cells (Zachos et al, 2007) and in U2OS cells (Carrassa et al, 2009). Here, our data provide in vivo evidence that Chk1 is essential for the spindle checkpoint in mouse mammary epithelial cells and mammary cancer cells.…”
Section: Discussionsupporting
confidence: 61%
“…Haploid loss of Chk1 impaired the spindle checkpoint It was shown previously that Chk1 deficiency in yeast and chicken DT40 cells caused defective spindle checkpoint (Collura et al, 2005;Zachos et al, 2007). As Chk1 þ /À cells exhibited mitotic catastrophe, we suspected that the spindle checkpoint might be impaired in these cells.…”
Section: Chk1 Haploinsufficiency and Mammary Tumorigenesis T Fishler mentioning
confidence: 83%
“…In addition, the Chk1-shRNA cells displayed elevated apoptosis rate and lower rate of G2/M cell cycle arrest, whereas the apoptosis and cell cycle analysis failed to find significant difference between Chk2-shRNA GSCs and normal GSCs. Our results are in line with previous studies, which have reported that Chk1 plays a key regulatory role in the G2/M DNA damage checkpoint (Zachos et al 2005;Zachos et al 2007). Besides Chk1, Chk2 has also been shown to be involved in the DNA damage signal transduction of the G1 and G2/M checkpoints, which is varied from Chk1 (Ahn et al 2003;Varmark et al 2010).…”
Section: Discussionsupporting
confidence: 83%
“…We observed robust spindle checkpoint responses in the absence of Pcnt, contrary to what has been described in Chk1 −/− DT40 cells. 42 Furthermore, the DNA damage checkpoint that blocks mitotic entry is intact GAA AGA GGA CAC-3'. The two homology arms and the tag were cloned into pBluescript using SpeI/BamHI, BamHI/XhoI and XhoI/KpnI digests for assembly.…”
Section: Methodsmentioning
confidence: 99%